Belief of Sri Lankan medical students about wife beating - Haj-Yahia, M.M.; De Zoysa, P. (My University, 2007)
The article presents the results of a study on beliefs about wife beating conducted among 476 Sri Lankan medical students. Participants fill out a selfadministered questionnaire, which examines six beliefs about wife beating. Most students tend to justify wife beating, to believe women benefit from wife beating, and to believe the wife bears more responsibility than the husband for violence against her. At the same time, most participants express willingness to help battered women. However, the vast majority oppose divorce as a solution to wife beating and are against punishing violent husbands. The results also reveal that a significant amount of the variance in each of the six beliefs are best explained by the students’ patriarchal approach toward women and marriage and by their exposure to violence in their families of origin. The implications of the results for future research and theory development on beliefs about wife beating are discussed.